Delivering Digital Climate Services to Smallholder farmers in Ethiopia - Endrias, Abrhame; Tesfaye, Kindie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
One of the overall project components for the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project is supporting the generation and sharing of knowledge tools to address critical gaps in the provision of climate advisory services, enable climate-informed investment planning and contribute to the design of policies to the uptake of climate-smart agricultural practices.